A novel dispatching rule for semi-heterarchical architectures in the Industry 4.0 context. Issue 1 (2021) - Vespoli, Silvestro; Scarpati, Miriam; Guizzi, Guido; Grassi, Andrea
Abstract: Industry 4.0 is changing the way to produce, pursuing increased flexibility of production systems and an ever-greater decision-making autonomy of the machines. The aim is to achieve high level of performances even in market scenarios requiring high level of customization, as the Mass Customisation (MC) paradigm imposes. Current hierarchical Manufacturing Planning and Control (MPC) systems showed limits in catching this goal, primarily due to their structural lack of flexibility. For this reason, the interest in the hybrid MPC architectures like the semi-heterarchical one is increasing. The objective of this work is to contribute to the design of such an architecture, proposing a new scheduling mechanism for the lowest decisional level. This mechanism, differently from the ones already proposed in the literature, schedules the next jobs to be admitted in the system choosing them by couples. The proposed rule has been tested through a simulation environment in three different scenarios of demand generation rate. The results showed an improvement in demand absorption and productivity compared to the rules used up to now.